Differences in Eating Quality Attributes between Japonica Rice from the Northeast Region and Semiglutinous Japonica Rice from the Yangtze River Delta of China - Ying Zhu (MDPI AG, 2021)
Differences in cooked rice and starch and protein physicochemical properties of three japonica rice were compared systematically. Cultivars of japonica rice, Daohuaxiang2, from Northeast China (NR) and two semiglutinous japonica rice (SGJR), Nangeng46 and Nangeng2728, from the Yangtze River Delta (YRD) were investigated. Both Daohuaxiang2 and Nangeng46 achieved high taste values, but there were great differences in starch and protein physicochemical properties. Daohuaxiang2 showed higher apparent amylose content (AAC), lower protein content (PC), and longer amylopectin (especially fb2 and fb3) and amylose chain lengths, resulting in thicker starch lamellae and larger starch granule size. Its cooked rice absorbed more water and expanded to larger sizes. All of these differences created a more compact gel network and harder but more elastic cooked rice for Daohuaxiang2. Nangeng46 produced a lower AAC, a higher PC, shorter amylopectin and amylose chain lengths, thinner starch lamellae, and smaller starch granule sizes, creating a looser gel network and softer cooked rice. The two SGJR, Nangeng46 and Nangeng2728, had similar low AACs but great differences in taste values. The better-tasting Nangeng46 had a lower PC (especially glutelin content) and higher proportion of amylopectin fa chains, which likely reduced the hardness, improved the appearance, and increased the adhesiveness of its cooked rice. Overall, both types of japonica rice from the NR and YRD could potentially have good eating qualities where Nangeng46’s cooked rice was comparable to that of Daohuaxiang2 because of its lower AC. Moreover, its lower PC and higher proportion of amylopectin fa chains likely improved its eating quality over the inferior-tasting SGJR, Nangeng2728. This research lays a foundation for the improvement of the taste of japonica rice in rice breeding.